Diseño e implementación de un prototipo para el ensamble de arandelas en clavos para la Instalación de láminas onduladas de zinc - Pérez Jiménez, Edgardo José; Quintana Ramos, Marlon Andrés (Universidad Antonio Nariño, 2022)
The following project develops an automatic prototype for the assembly of rubber washers on nails used for the installation of zinc sheets for the construction of roofs, which is aimed at hardware stores and small companies in the construction sector. The design of the automatic prototype is simple, low-cost and efficient that allows assemblies in less time with respect to the manual assembly process that is currently carried out and therefore, it aims to reduce the production costs of the companies.